Recent trends in cardiac electrophysiology and catheter ablation in New Zealand. Issue 10 (27th October 2020) - Foo, Fang Shawn; Stiles, Martin K.; Clare, Geoffrey C.; Lever, Nigel; Hooks, Darren; Heaven, David; Boddington, Dean
Abstract: Background: Catheter ablation has rapidly become an integral part of the management of many arrhythmias. Aims: To provide a history of clinical cardiac electrophysiology (EP) in New Zealand (NZ) and analysis of recent trends in EP procedures and catheter ablations across NZ, which has not previously been reported. Methods: EP case type and volume were obtained from the EP databases from each of the four public and four private EP centres in NZ from 1 January 2014 to 31 December 2018. Procedure rates were expressed as per million population. Results: A total of 7695 EP cases was performed, including 5929 (77%) in the public sector. Atrial fibrillation (AF) ablation was the most common procedure at 29%. EP procedure rates increased by 21% (to 353 per million in 2018), predominantly due to AF ablation rates increasing by 46%. Ventricular tachycardia ablation rates increased by 41% but only comprised 8% of procedures. There was a striking difference in the growth of EP procedure rates in the public compared to the private sector (4% vs 106%), as well as considerable differences in EP procedure and AF ablation rates across the public EP centres. NZ had lower ablation rates compared to countries with similar healthcare expenditure. Conclusion: There has been a substantial increase in EP procedure and AF ablation rates in NZ and international trends suggest this growth will continue. However, there is considerable variation in procedure rates and growth trends between EP centres, highlighting inequities in access within the country.